Implementasi Model Pembelajaran Beyond Center And Circle Time (BCCT) Sebagai Upaya Meningkatkan Kualitas Pendidikan - Romini Romini (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2021)
This study aims to improve the quality of education in the integrated Pniel Chiristian Kinderagarten to make it more interesting, child-centred learning, and more creative learning, and more creative learning activities. Through implementation of the Beyond Center and Circle Time (BCCT) learning model, it is hoped that it can improve the quality of education in the integrated Peniel Christian Kindergarten. The research method used was school Action Research (PTS) with teacher six apprentices, an six TOT as the research subjects. Collecting data through observation, interviews, and documentation in the form of records of child development. Te study was conducted in three cycles. The results obtained through interview with 5 Kindergarten teacher of peniel stated that: learning activities are more fun, children are more creative and play according to their interests, and children tend to want to try every variety of play facilitatated by the teacher. Children are seen to be more independent because they do their own activities and children prefer to play in the center, so that children can develop their creativity. Teachers are also motivated to facilitate in preparing various games, develop children ‘s intellgence based on multiple intelegences, teachers focus more on center, so that it is more fun. Paring various games, develop children’s intelligence based on multiple intelligences, teachers focus more on one center, so that it is more fun to accompany children ti learn, can make objects around them as a means of learning while playing. The central learning room is equipped with appropriate and supportive play, facilities. From the 12 training participants stated: through the implementation of learning with beyond Center and circle Time (BCCT), the quality of education in the integrated Pniel Chritian Kindergarten can be increased, so that the Integrated Pniel Christian Kindergarten is chosen to be a Kindergarten pilot at the PESAT Foundation and become a training ground for PESAT kindergarten teachers. AbstrakPenelitian ini bertujuan untuk meningkatkan kualitas pendidikan di TK Kristen Pniel Terpadu agar makin menarik, pembelajaran berpusat pada anak, dan kegiatan pembelajaran makin kreatif. Melalui Implementasi model pembelajaran Beyond Center and Circle Time (BCCT) di harapkan dapat meningkatkan kualitas Pendidikan di TK Kristen Pniel Terpadu. Metode penelitian digunakan dengan Penelitian Tindakan Sekolah (PTS) dengan subyek penelitian lima guru, enam peserta magang, dan enam peserta peserta TOT. Pengumpulan data melalui observasi, wawancara, dan dokumentasi berupa catatan perkembangan anak. Penelitian dilakukan dengan tiga siklus hasil yang diperoleh melalui wawancara kepada 5 guru TK Pniel menyatakan bahwa: kegiatan pembelajaran semakin menyenangkan, anak lebih kreatif dan bermain sesuai minatnya, dan anak cenderung ingin mencoba setiap ragam main yang difasilitasi guru. Anak lebih terlihat kemandiriannya karena melakukan kegiatan sendiri dan anak lebih senang bermain di sentra, sehingga anak dapat mengembangkan kreatifitasnya. Guru pun termotivasi untuk memfasilitasi dalam menyiapkan ragam permainan, mengembangkan kecerdasan anak berdasarkan kecerdasan majemuk, guru lebih fokus di satu sentra, sehingga lebih asyik dalam mendampingi anak belajar, dapat menjadikan benda-benda yang ada disekitar sebagai sarana belajar sambil bermain, ruang belajar/sentra diperlengkapi dengan sarana main yang sesuai dan mendukung. Dari 12 orang peserta training menyatakan: melalui penerapan pembelajaran dengan Beyond Center and Circle Time (BCCT) maka kualitas pendidikan di TK Kristen Pniel Terpadu dapat meningkat, sehingga TK Kristen Pniel Terpadu dipilih menjadi TK percontohan di Yayasan PESAT dan menjadi tempat pelatihan para-guru TK PESAT.